Choledocholithiasis with hepatolithiasis: spontaneous passage of a string of pearls - Watter, Henry K.; Munugani, Suresh (International Surgery Journal, 2023)
Choledocholithiasis is known to pass spontaneously in a large proportion of patients. This case report documents extensive choledocholithiasis and hepatolithiasis presenting as gallstone pancreatitis in a 37-year-old female. All ductal stones (>15 stones measuring up to 10 mm) had passed spontaneously at the time of endoscopic retrograde cholangiopancreatography, 10 days after presentation. No previous case reports document this number, size and location of ductal stones passing spontaneously.